Characteristics of the paravertebral muscle in adult degenerative scoliosis with PI-LL match or mismatch and risk factors for PI-LL mismatch - Guo, Jichao; Xie, Dongxiao; Zhang, Jinniu; Ding, Wenyuan; Zhao, Boyang; Li, Zhaohui; Huo, Yachong (Frontiers in Surgery, 2023)
Objective: PI-LL correlates with function and disability, is associated with PVM degeneration, and is a valuable tool for surgical planning of ADS. The study was designed to explore the characteristics of PVM in ADS with a PI-LL match or mismatch and to identify the risk factors for a PI-LL mismatch. Methods: 67 patients with ADS were divided into PI-LL match and mismatch group. The percentage of fat infiltration area (FIA) of multifidus at L1–S1 disc level was measured by MRI, using Image-J software. SVA, LL, PT, PI, SS, and the asymmetric and average degeneration degrees of multifidus were recorded. Logistic regression analysis was to identify the risk factors of PI-LL mismatch. Results: In the PI-LL match and mismatch group, the average FIA% of multifidus on the convex side was less than on the concave (P<0.05). There was no statistical difference in the asymmetric degeneration degree of multifidus between the two groups (P>0.05). Average degeneration degree of multifidus in the PI-LL mismatch group was significantly higher than PI-LL match group (32.22±6.98 vs 26.28±6.23 (%), P<0.05). Sagittal plane balance, LL, PT and average degeneration degree of multifidus were the risk factors of PI-LL mismatch (OR: 15.447, 95%CI: 1.274~187.269; OR: 0.001, 95%CI: 0.000~0.099; OR: 107.540, 95%CI: 5.195~2225.975; OR: 52.531, 95%CI: 1.797~1535.551, P<0.05). Conclusion: PVM on the concave side was larger than on the convex side in ADS, whether PI-LL was matched or not. A PI-LL mismatch could aggravate this abnormal change that is an important reason for pain and disability in ADS. Sagittal plane imbalance, decreased LL, higher PT, and a larger average degeneration degree of multifidus were independent risk factors for PI-LL mismatch.